The Components of Abstracts in the Areas of Indonesian International Journals - Asbah Asbah; Lalu Isnaeni Rahman (Linguistics and ELT Journal, 2020)
The readers prefer to read the abstract in order to find out the contents. It has to be short, easily read, and understandable. It consists of complete elements or components. The aimed of this study were to reveal the components of abstract and to find out what were patterns of moves. The researchers used descriptive qualitative approach because this study focused on the analysis or interpretation of the written material in context. Quirkos Application was used to sort, manage, analyzed and understand the data. From the results that already exist, there are thirteen procedures of writing abstracts used by writers in Indonesian International Journals Indexed Scopus. Those were I, IP, IR, IPR, IRD, IMR, PMR, PMD, IMRD, PMRD, IPMR, PIRM, and IPMRD. There are limitations in this research that have to be considered. First, this corpus consists of abstracts in only areas of Indonesia. Second, further research is necessary to determine the variables that affect the writers’ model in writing an appropriate abstract. Thirdly, the researchers only analyzed 47 abstracts.